### Discussion :: Logarithm - General Questions (Q.No.1)

K.Manohar Reddy said: (May 22, 2011) | |

Its absolutely correct. |

Begum said: (Aug 21, 2011) | |

Its great. |

Venu said: (Oct 2, 2014) | |

If they say log 6 = log 2 + log 3, then log (2+3) = log 2 + log 3. Can someone explain ? |

Vikash said: (Oct 20, 2014) | |

log 6 = log(2*3) = log 2 + log 3. But log(2+3) =log 5 which is not equal to log 6. So, log(2+3) != log 2 + log 3. |

Tendai said: (Jan 18, 2015) | |

What about 243 base 9? |

Akshayaa said: (Mar 19, 2015) | |

What about 828 with base 2? |

Murali said: (Jul 6, 2015) | |

243 base 9. This mainly 243 = 3*3*3*3*3 = 3^5. And 9 = 3*3 = 3^2. So answer is 5/2. I dot no how to write log in keyboard. |

Palak Kapoor said: (Oct 1, 2015) | |

If a=5 and b=4 then what is the value of log (a-b) (a^2-b^2-2^b)? |

Shashi said: (Oct 4, 2015) | |

Its awesome. |

Ssd said: (Oct 13, 2015) | |

What is log to the base 5 512? |

Garvit said: (Jan 18, 2016) | |

Option D can't be considered answer. It's tricky actually: LHS: log (1+2+3) = log 6. [1+2+3 = 6]. RHS: log1 + log2 + log3 = log (1x2x3) = log 6. Since LHS = RHS (no matter how it comes) D isn't the option. |

Suhaas said: (May 1, 2016) | |

@Palak Kapoor. The answer is undefined. log{5 - 4}[5^2 - 4^2 - 4] log{1}[25 - 16 - 16] log[25 - 32] log[- 7] log value for -ve is undefined. |

Sylvester said: (Jun 13, 2016) | |

The given answer is absolutely correct. |

Meenakshi said: (Jul 19, 2016) | |

The anwer is absolutely correct according to log properties. It's log a + log b = log(a * b). not log(a + b) = log(ab). |

Ravi said: (Dec 3, 2016) | |

@all. B is absolutely correct. |

Disha Jhan said: (Mar 11, 2017) | |

The answer B is correct. I agree with it. |

Isaac said: (Mar 14, 2017) | |

Can someone help me understand how D is a true statement? If log6=10^6=1,000,000 how is that equal to log1+log2+log3? =10^1+10^2+10^3, =10+100+1000, =1110. |

Sanyal said: (Mar 14, 2017) | |

Correct, Thanks for the given explanation. |

Dhaval said: (Nov 23, 2017) | |

D is also incorrect. log(1+2+3) = log 1* log 2 * log 3. |

Riya Raj said: (Mar 15, 2018) | |

I'm also confused because it both the cases results are coming the same soo however it's different. Please explain me. |

Deepak said: (May 6, 2018) | |

I am not understanding this. Can anyone explain by taking general variable? |

Kity said: (Jun 14, 2018) | |

How, Please explain this. |

Abhishek said: (Aug 6, 2018) | |

The answer B is correct. I agree with it. |

Omkar Rajale said: (Aug 24, 2018) | |

Please explain the option D. |

Keerthana said: (Jan 31, 2019) | |

Thanks all for explaining. |

Shivam Ghorpade said: (Jun 30, 2019) | |

Thanks all for explaining. |

Sneha said: (Apr 29, 2020) | |

Thanks for the explanation. |

Girmay Yohanness said: (May 6, 2020) | |

Thanks for the explanation. |

Swaroop said: (Jul 1, 2020) | |

According to me, Option B and D, both are incorrect. |

Swaroop said: (Jul 1, 2020) | |

Answer D is correct too, since. log(1+2+3)=log(6)=log(1*2*3)=log1+log2+log3. |

#### Post your comments here:

Name *:

Email : (optional)

» Your comments will be displayed only after manual approval.